2001
DOI: 10.1111/j.1748-0361.2001.tb00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Important Retention and Recruitment Factors by Therapists in Northwestern Ontario

Abstract: Recruitment and retention of health professionals in rural and remote communities are well-known challenges. Although the literature states that lifestyle factors and being from a rural background influence recruitment and retention, much of the research is dated and of limited relevance to rehabilitation professionals. This study reports on a survey of physical therapists (PTs) and occupational therapists (OTs) in northwestern Ontario. Seventy-four percent of the OTs and PTs from this geographically isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 19 publications
2
34
2
Order By: Relevance
“…The opportunity for career development continued to be the most significant predictor of job turnover and regional attrition. Similarly, Solomon and colleagues 24 found that the top five sources of job dissatisfaction among all practising occupational therapists and physiotherapists in northwestern Ontario were lack of opportunity for continuing education; professional isolation; hours of work or clinical workload; lack of long-term security; and lack of opportunity for promotion. On the basis of our study's findings and those of previous research, developing rural and remote workforce strategies for rehabilitation therapists should be one of the priority areas in HHR planning.…”
Section: Discussionmentioning
confidence: 98%
“…The opportunity for career development continued to be the most significant predictor of job turnover and regional attrition. Similarly, Solomon and colleagues 24 found that the top five sources of job dissatisfaction among all practising occupational therapists and physiotherapists in northwestern Ontario were lack of opportunity for continuing education; professional isolation; hours of work or clinical workload; lack of long-term security; and lack of opportunity for promotion. On the basis of our study's findings and those of previous research, developing rural and remote workforce strategies for rehabilitation therapists should be one of the priority areas in HHR planning.…”
Section: Discussionmentioning
confidence: 98%
“…In nursing environments where this opportunity is afforded, the levels of occupational stress are lower [29]. In terms of quality of work life, studies have reported that increased job autonomy and job control is linked to higher QWL among nurses and allied health professionals [30,31]. It is hypothesized that location of cross-training will afford nurses with increased clinical competencies to work in all areas of the birthing unit and permit for greater decisionmaking capacity in the delivery of obstetrical care to their patients.…”
Section: Materials and Methods Designmentioning
confidence: 99%
“…Literature exists describing barriers to CPD for physiotherapists (Titchen 1987;Spalding et al 1999;Pringle and Moore 2001;O'Sullivan 2003) however little refers to CPD and physiotherapists in the context of lone practice (Bithell and Minns Lowe 2000;Solomon et al 2001) and none relates to physiotherapists working in amputee rehabilitation. There are examples of how CPD is or could be achieved for health professionals, however in these studies the context is primarily in relation to geographical isolation (Dunning et al 1994;Bithell and Minns Lowe 2000;Parkin et al 2001).…”
Section: Physiotherapists Amputee Rehabilitation and Lone Workingmentioning
confidence: 99%
“…In DSCs the amputee physiotherapist may be the only physiotherapist. Whilst not necessarily geographically isolated, they can be described as lone practitioners in that they are professionally isolated and face a deficiency in available colleagues with whom they can relate, or a lack of involvement with peers of the same profession (Shreffler 1992;Solomon et al 2001). Whilst there are some benefits to lone working such as greater independence and autonomy (Davis and Droes 1993), lone practitioners can face considerable challenges, such as little peer support, review or relevant supervision (Bithell and Minns Lowe 2000).…”
Section: Physiotherapists Amputee Rehabilitation and Lone Workingmentioning
confidence: 99%